Дослідження методів визначення ефективності ІТ-аутсорсингу - Назаренко, Станіслав Миколайович; Перерва, Петро Григорович (Національний технічний університет "Харківський політехнічний інститут", 2021)
В статті окреслено певні проблеми при визначенні ефективності аутсорсингових відносин, з яких запропоновано виділити наступні. По-перше, на сьогоднішній день не існує узагальнюючих публікацій, в яких були б систематизовані і детально описані інструменти економічної оцінки ІТ-аутсорсингу, відповідна інформація розкидана по великій кількості статей і монографій. Внаслідок цього фахівці з аутсорсингу позбавлені можливості порівняти різні інструменти і вибрати найбільш підходящий і нерідко виявляються змушені самостійно розробляти відповідний інструментарій. По-друге, зазвичай пропоновані методики носять загальний характер і не адаптовані до специфіки певної галузі або конкретного підприємства.

A study of existing publications has revealed a significant number of tools aimed at effective management of outsourcing relationships. The article outlines certain problems in determining the effectiveness of outsourcing relationships, of which it is proposed to highlight the following. First, to date, there are no generalized publications that would systematize and describe in detail the tools of economic evaluation of IT outsourcing, the relevant information is scattered over a large number of articles and monographs. As a result, outsourcing professionals are deprived of the opportunity to compare different tools and choose the most appropriate and often have to develop their own tools. Secondly, usually the proposed techniques are general in nature and not adapted to the specifics of a particular industry or specific enterprise. As a result, an enterprise or organization wishing to use IT outsourcing in its activities will face the need to adapt existing techniques to the specific situation. There is no single method of calculating the economic effect of outsourcing. The conducted researches allow to draw a conclusion that at present two criterion approaches to an estimation of efficiency of outsourcing exist and are actively used: single-criteria and multicriteria. In the case of a decision using one criterion, most often use a certain financial indicator (indicator), which indicates the possible savings due to the use of IT outsourcing. As a result of the presence of significant shortcomings in the use of single-criteria methods of acceptance in the practice of industrial enterprises began to use multi-criteria methods to assess the effectiveness of IT outsourcing. This group of methods allows us to assess the integrated effect of the use of IT outsourcing. The multi-criteria methodological approach is based on the convolution of a certain set of partial indicators that assess the different types of economic effect from the use of IT outsourcing into a single comprehensive indicator. The study concludes that the use of both numerical and graphical methods for evaluating the effectiveness of IT outsourcing provides some positive results for the top management of the enterprise and increases the accuracy and objectivity of management decisions. However, these decisions would be more reasonable when used to assess the effectiveness of IT outsourcing integrated methodology, as if it combined both quantitative and graphical elements.
Research of methods for determining the efficiency of it outsourcing
Keywords: аутсорсинг; інформаційні технології; ефективність; методи; промислові підприємства; outsourcing; information technology; efficiency; methods; industrial enterprises